Influence of anthropic activities on the functional diversity of aquatic macroinvertebrates in the Lower Rio Grande Basin (Research, Society and Development, 2022)
Functional diversity takes into account the differences in ecological functions that organisms perform in a community, and these can influence its structural stability. In this context, anthropic pressures significantly affect the ecosystem functions performed by organisms. In this sense, it was hypothesized that anthropic impacts directly and negatively influence the functional structure of the aquatic macroinvertebrate community in different stretches of the Uberaba River, which is a tributary of the lower Rio Grande Basin. To evaluate functional diversity, sampling was carried out in four distinct stretches and in different seasonal periods. A Non-Metric Multidimensional Scaling (NMDS) similarity analysis was performed for all sites and periods, based on a functional matrix with forty-three biotic attributes. Based on the NMDS results, niche areas were calculated. Finally, a comparative analysis of the functional parameters: Abundance, Richness, Functional Equitability, Shannon Functional Diversity, Simpson Functional Diversity and Functional Dominance between all sites and all seasonal periods was performed. The results showed that anthropic activities negatively influenced the functional diversity of the aquatic macroinvertebrate community according to its intensity.